Cell competition overcomes host tissue resistance to unleash tumor growth in a Drosophila brain cancer model - Marco Gualtieri; Saline Jabre; Damien Mornico; Maëlwenn Hamon; Gaëlle Letort; Cédric Maurange; Pauline Spéder (Proceedings of the National Academy of Sciences, 2026)
Primary tumors of the central nervous system are extremely aggressive and often incurable. While tumor cells are known to interact with their microenvironment, the complexity and temporal dynamics of this interplay and its impacts on tumor progression remains to be fully understood. We addressed this question in a Drosophila model of cancer stem cell–driven tumor which originates during development and grows extensively within a network of cortex glia cells through adulthood. We revealed a biphasic interplay between tumor and cortex glia cells, characterized by morphological, molecular, and functional changes. In early stages, glial cells infiltrate the tumor, display a distinct transcriptional signature, and resist its growth, supported by the intrinsic neuroprotective activity of the c-Jun N-terminal kinase (JNK) signaling pathway. However, cancer stem cell–driven competition takes place, eliminating cortex glia by apoptosis and ultimately unleashing tumor growth. This second phase sees the breakdown of the glial meshwork and adhesions to neurons, along with the downregulation of the JNK pathway and a decline in essential cellular functions. Ultimately, the host tissue collapses, in turn curbing tumor growth. This study uncovers a dynamic and complex interplay between host tissue resistance and tumor-driven competition, which shapes tumor progression.